2022
DOI: 10.2196/22124
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Health Information Technology in Supporting Health Equity for Black and Hispanic Patients With Chronic Diseases: Systematic Review

Abstract: Background Racial inequity persists for chronic disease outcomes amid the proliferation of health information technology (HIT) designed to support patients in following recommended chronic disease self-management behaviors (ie, medication behavior, physical activity, and dietary behavior and attending follow-up appointments). Numerous interventions that use consumer-oriented HIT to support self-management have been evaluated, and some of the related literature has focused on racial minorities who e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 79 publications
(76 reference statements)
1
2
0
Order By: Relevance
“…Overall, our results suggest that women with chronic conditions were more likely to report using digital health tools than those without these conditions. These findings are similar to previous studies showing increased digital health use, especially among those with chronic diseases [19,[23][24][25]. A difference in digital health use was also noted based on the type of condition reported.…”
Section: Principal Findingssupporting
confidence: 90%
See 1 more Smart Citation
“…Overall, our results suggest that women with chronic conditions were more likely to report using digital health tools than those without these conditions. These findings are similar to previous studies showing increased digital health use, especially among those with chronic diseases [19,[23][24][25]. A difference in digital health use was also noted based on the type of condition reported.…”
Section: Principal Findingssupporting
confidence: 90%
“…For instance, older adults are an at-risk cohort with higher disease rates and more health care needs, as well as the fastest growing group, yet they are largely disconnected from the digital world [ 19 , 23 ]. Low-income minority groups experience barriers due to the limited availability and affordability of mobile services and internet limitations [ 24 ]. In this current age of technology, digital inclusion and literacy have been deemed “super social determinants of health” as they address all other health determinants [ 11 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…These organizations also agree that work needs to be done on understanding the reasons underlying the causes of these disparities, stating that clinical trials specifically take steps to address the disparity data collected, and that outreach to these communities needs to be undertaken in non-traditional settings (churches and barbershops for example). Furthermore, a concerted effort to use mobile health technology, and effective interventions by non-physicians to reach disparity groups needs to be made to ensure these members of society do not continue to be left behind [49][50][51]. Experts have even suggested that priority should be given to culturally tailored interventions to decrease the incidence of recurrent stroke in underserved populations [7].…”
Section: Discussionmentioning
confidence: 99%